Microbial Mechanistic Insight into the Role of Yeast−Derived Postbiotics in Improving Sow Reproductive Performance in Late Gestation and Lactation Sows - Junlei Chang; Xinlin Jia; Yalei Liu; Xuemei Jiang; Lianqiang Che; Yan Lin; Yong Zhuo; Bin Feng; Zhengfeng Fang; Jian Li; Lun Hua; Jianping Wang; et al. (Animals, 2024)
The purpose of this study is to investigate the effects of supplementing Yeast−derived postbiotics (Y−dP) to the diet of sows during late pregnancy and lactation on fecal microbiota and short−chain fatty acids (SCFA) in sows and their offspring weaned piglets, as well as the relationship between gut microbiota and SCFA, serum cytokines, and sow reproductive performance. A total of 150 sows were divided into three groups: control diet (CON), CON + Y−dP 1.25 g/kg, and CON + Y−dP 2 g/kg. The results showed that supplementing 0.125% Y−dP to the diet of sows can increase the content of isobutyric acid (IBA) in the feces of pregnant sows and reduce the content of butyric acid (BA) in the feces of weaned piglets (p < 0.05). The fecal microbiota of pregnant sows β diversity reduced and piglet fecal microbiota β diversity increased (p < 0.05). Y−dP significantly increased the abundance of Actinobacteria and Limosilactobacilli in the feces of pregnant sows (p < 0.05), as well as the abundance of Verrucomicrobiota, Bacteroidota, and Fusobacteriota in the feces of piglets (p < 0.05). The abundance of Bacteroidota in the feces of pregnant sows is positively correlated with propionic acid (PA) (r > 0.5, p < 0.05). The abundance of Prevotellaceae_NK3B31_group was positively correlated with Acetic acid (AA), PA, Valerate acid (VA), and total volatile fatty acid (TVFA) in the feces of pregnant sows (r > 0.5, p < 0.05), and Bacteroidota and Prevotellaceae_NK3B31_group were negatively correlated with the number of stillbirths (r < −0.5, p < 0.05). The abundance of Lactobacillus and Holdemanella in piglet feces was positively correlated with TVFA in feces and negatively correlated with IgA in serum (r > 0.5, p < 0.05). In conclusion, supplementing Y−dP to the diet of sows from late gestation to lactation can increase the chao1 index and α diversity of fecal microorganisms in sows during lactation, increase the abundance of Actinobacteria and Limosilactobacilli in the feces of sows during pregnancy, and increase the abundance of beneficial bacteria such as Bacteroidetes in piglet feces, thereby improving intestinal health. These findings provide a reference for the application of Y−dP in sow production and a theoretical basis for Y−dP to improve sow production performance.